(untitled) (Scientific journal of the Fergana State University, 2026)
In this study, the leaves of Origanum titthanthum (mountain basil) and Salvia officinalis (medicinal herb) were mixed in a 1:1 mass ratio to prepare a new food additive called “Oregano AS”. The product was subjected to drying, grinding, and homogenization processes. As a result of organoleptic, physicochemical, and microbiological analyses, it was determined that the preparation complies with hygiene standards and does not contain heavy metals and harmful microorganisms. The high content of polyphenols, flavonoids, and essential oils confirms the biological activity of the product. “Oregano AS” is recommended for use in the food industry as an environmentally friendly and promising additive.